Diversity and genetic connectivity of heteropod (Pterotracheoidea) gastropods in the Tropical Eastern Pacific. Issue 1 (14th March 2023) - Collin, Rachel; Madrid, Maycol; Venera‐Pontón, Dagoberto E.; Macdonald, Kenneth S.; De León, Alexandra; Vrdoljak, Dubravka; Boyle, Michael J.; Bryant, Peter; Arehart, Tim; Driskell, Amy C.
Abstract: Previous research focusing on pelagic gastropods in the open ocean has demonstrated that many morphospecies comprise multiple distinct clades or cryptic species that can be distinguished with DNA sequence data. To date, the genetic diversity of the pelagic gastropod fauna of the tropical East Pacific, especially in shallow coastal waters, remains largely unexplored. To document the diversity of pterotracheoids (formerly heteropods) from the coastal waters of the Bay of Panama, we collected, photographed and sequenced fragments of mitochondrial cytochrome c oxidase subunit I ( COI ) and 16S ribosomal DNA for 60 atlantids, 3 carinariids and 6 pterotracheids. In addition to the COI barcode, our results include the first published 16S sequences for these groups. We found 11 operational taxonomic units (OTUs): 9 in the genus Atlanta, 1 Carinaria and 1 Firoloida . We report the presence of Atlanta oligogyra (Clades A and B), Atlanta turriculata, Atlanta lesueurii, Atlanta helicinoidea (Clade B), Atlanta plana, Atlanta echinogyra, Atlanta inflata and Atlanta frontieri through comparisons of our sequences with previously published sequences. We did not find Atlanta gaudichaudi, Atlanta inclinata, Atlanta tokiokai, Atlanta gibbosa, Atlanta peronii, or Oxygyrus inflatus, which have previously been reported from the region. Haplotype networks and estimates of ΦST illustrate how some species show population differentiation across the tropical Indo‐Pacific region, whereas others show little apparent population structure. For example, the most common haplotypes of A . inflata and of A . turriculata occur in the Indian Ocean, the Central and West Pacific and the tropical East Pacific, whereas individuals of A . frontieri from the Indian Ocean do not share haplotypes with individuals of A . frontieri from the Pacific Ocean. Analyses were limited by sample sizes, but these data suggest that population genetics approaches may be useful for reconstructing population histories of these important, but overlooked, components of the plankton. Resumen: Investigaciones previas enfocadas en gasterópodos pelágicos en mar abierto han demostrado que muchas morfoespecies se componen de múltiples clados distintos o especies crípticas que se pueden distinguir con datos de secuencia de ADN. Hasta la fecha, la diversidad genética de la fauna de gasterópodos pelágicos del Pacífico Oriental Tropical, especialmente en aguas costeras poco profundas, permanece en gran parte sin explorar. Para documentar la diversidad de pterotraqueoides (anteriormente heterópodos) de las aguas costeras de la Bahía de Panamá, recolectamos, fotografiamos y secuenciamos fragmentos de la subunidad I (COI) del citocromo c oxidasa mitocondrial y el ADN ribosomal 16S de 60 atlántidos, 3 carináridos y 6 pterotraqueidos. Además del código de barras COI, nuestros resultados incluyen las primeras secuencias de 16S publicadas para estos grupos. Encontramos 11 unidades taxonómicas operativas (UTO), 9 en el género Atlanta, 1 Carinaria y 1 Firoloida . Reportamos la presencia de Atlanta oligogyra (clados A y B), Atlanta turriculata, Atlanta lesueurii, Atlanta helicinoidea (Clade B), Atlanta plana, Atlanta echinogryra, Atlanta inflata y Atlanta frontieri mediante comparaciones de nuestras secuencias con secuencias publicadas previamente. No encontramos Atlanta gaudichaudi, Atlanta inclinata, Atlanta tokiokai, Atlanta gibbosa, Atlanta peronii ni Oxygyrus inflatus, que han sido reportadas previamente en la región. Las redes de haplotipos y las estimaciones de FST ilustran cómo algunas especies muestran diferenciación poblacional en la región tropical del Indo‐Pacífico, mientras que otras muestran poca estructura poblacional aparente. Por ejemplo, los haplotipos más comunes de A . inflata y de A . turriculata se encuentran en el océano Índico, el Pacífico central/occidental y el Pacífico oriental tropical, mientras que A . frontieri del océano Índico no comparte haplotipos con individuos de A . frontieri del Océano Pacífico. Los análisis estuvieron limitados por el tamaño de las muestras, pero estos datos sugieren que los enfoques de genética de poblaciones pueden ser útiles para reconstruir las historias de población de estos componentes importantes, pero pasados por alto, del plancton.